CHANGING DEMOGRAPHICS - IMPLICATIONS FOR HOUSEHOLD PORTFOLIOS - Tripathi, Sanjay (2010)
Households have a hump shaped income profile with respect to age, which means that younger households have lower income that increases with age, the income stabilizes in the middle years and starts to decline post retirement. The income lifecycle is inversely proportional to risk aversion which plays an important role in how households allocate assets in their portfolio, low in younger years and gradually increasing with age that reaches its peak before it starts to drop off post retirement. The main objective of this study is to explore demographic trends like changing age structure and its impact on variability in household portfolio asset allocation by reviewing the current literature and available household data.